Indonesia’s Legal Policies Amid Covid-19 - Cekli Setya Pratiwi (University of Jember, 2022)
The Covid-19 pandemic has forced States to promulgate various legal policies to restrain public activities, including limiting or prohibiting people to exercise their right to religious freedom or beliefs (FoRB) in the public sphere and imposing repressive sanctions. International Human Rights Law (IHRL) regulates the standard limitation of FoRB, but the Government of Indonesia struggled to balance respecting FoRB and protecting public health, especially in the emergency of Covid-19. While the Government is oriented to protect public health, new violations of FORB add more backlog on unresolved cases. Through a Human Rights-Based Approach and case studies, three essential principles of FoRB, namely the principle of non-discrimination, the principle of proportional restriction, and the principle of non-coercion in religion, will be analyzed qualitatively to assess, first, the extent to which legal policies in Indonesia amid Covid-19 are compatible with IHRL. Second, the extent to which these legal policies impact the right to religious freedom of the people. Third, to ask the question: how should the legal policies in the Covid-19 era be formulated so that the State can balance the protection of public health and religious freedom? Keywords: Covid-19, the right to freedom of religion or belief, the right to public health, derogation, limitation.